Achatina fulica Mucus Ameliorates UVB-induced Human Dermal Fibroblast Photoaging via the TGF-β/Smad Pathway - Christiana Tri Nuryana; Tiara Puspita Agustin; Sofia Mubarika Haryana; Yohanes Widodo Wirohadidjojo; Nur Arfian (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Ultraviolet B (UVB) induces skin photoaging by reducing collagen deposition via impairment of the TGF-β/Smad signaling pathway. Achatina fulica mucus (AFM) is a native medicine acting as vehicle of anti-aging ingredients. The present investigation examined the effect of AFM on UVB-induced fibroblast photoaging by assessing TGF-β, Smad3, and Smad7 mRNA expressions.METHODS: AFM was extracted from A. fulica using electrical shock and freeze-dried into a powder. Normal human dermal fibroblast (NHDF) cultures were irradiated with/without 100 mJ/cm2 UVB and treated with/without 10% platelet-rich plasma or different concentrations of AFM: 3.9 μg/mL in AF3 group; 15.625 μg/mL in AF15 group, and 62.5 μg/mL in AF62 group. The mRNA expressions of TGF-β, Smad3, and Smad7 in NHDF were evaluated by quantitative polymerase chain reaction.RESULTS: TGF-β mRNA expressions in the AF3 (0.85±0.01), AF15 (0.94±0.02) and AF62 (1.64±0.03) groups were significantly higher (p<0.05) compared with that in the UVB group (0.55±0.04). Moreover, Smad3 expressions in the AF3 (1.42±0.25), AF15 (1.89±0.13), and AF62 (2.50±0.31) groups were significantly higher (p<0.05) compared with that in the UVB group (0.57±0.08). Furthermore, Smad7 expressions in the AF3 (1.57±0.18), AF15 (0.87±0.03), and AF62 (0.25±0.09) groups were significantly lower (p<0.05) than that in the UVB group (2.57±0.06).CONCLUSION: AFM ameliorates UVB-induced fibroblast photoaging by upregulating the TGF-β/Smad3 expressions and downregulating Smad7 expression.KEYWORDS: Achatina fulica, TGF-β, Smad, collagen, UVB, fibroblast, photoaging